2021
DOI: 10.1016/j.jaccao.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Transplantation and Mechanical Circulatory Support in Amyloidosis

Abstract: Central Illustration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Hence, it is imperative to diagnose ATTR-CM at earlier stages with available non-invasive testing and FDA approved treatments. Heart transplantation can be considered in select patients with Stage D HF[ 12 ]. The current allocation system provides priority as Status 4 to these stage D ATTR-CM patients due to a lack of durable mechanical support options[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is imperative to diagnose ATTR-CM at earlier stages with available non-invasive testing and FDA approved treatments. Heart transplantation can be considered in select patients with Stage D HF[ 12 ]. The current allocation system provides priority as Status 4 to these stage D ATTR-CM patients due to a lack of durable mechanical support options[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is reasonable to consider silencer therapy if patients have lifestyle-limiting neuropathy in the postheart transplant phase [64 ▪▪ ]. Historically, liver transplant was considered a first-line therapeutic modality in patients with hATTR to replace the source of mutant TTR production [62,64 ▪▪ ]. However, studies have shown that patients who underwent liver transplant continued to have amyloid deposition of the wild-type TTR subtype [62,66–68].…”
Section: Advanced Heart Failure Therapiesmentioning
confidence: 99%
“…Small left ventricular size presents technical challenges for inflow cannula placement and advanced stages of the disease are less responsive to mechanical support [62]. However, there may be a subset of patients with larger left ventricular cavities who may benefit, particularly when used as a bridge to transplant strategy [63,64 ▪▪ ]. Furthermore, RV failure is often progressive in this disease process, further underscoring the limitations of left sided ventricular support [62,63].…”
Section: Advanced Heart Failure Therapiesmentioning
confidence: 99%
See 2 more Smart Citations